Pollination in Plants - William Mokwala, Phatlane (IntechOpen, 2018)
Plants are the basic source of food for both humans and animals. Most of the food is made of fruits and seeds. For these to be formed, pollination must first take place. This process is the transfer of pollen grains from the anther, which is the male structure of the flower, to the sigma on the female structure of the flower. The transfer process requires agents to be carried out. The agents can be either biotic or abiotic. Nature perfected this arrangement between the pollination agents and the plants. As ecosystems and agricultural systems are changing, this balanced arrangement becomes disturbed. This makes it necessary that pollination systems be studied so that necessary measures can be undertaken to ensure productivity. The chapters of this book present results in research undertaken to improve productivity in crops such as Actinidia chinensis (the kiwifruit), Theobroma cacao (cocoa), and Manicaria saccifera (a tropical forest palm). Some results are presented on tests to check the viability of pollen grains and the delivery of sperm cells through pollen tubes to the embryo sac. These results can serve as guidelines to any person seeking to improve pollination and productivity or to check the efficiency on pollination in ecosystems or agricultural production systems.